Brain structure changes in nondemented seniors after six-month dance-exercise intervention - Rektorova, Irena; Klobusiakova, Patricia; Balazova, Zuzana; Kropacova, Sylvie; Sejnoha Minsterova, Alzbeta; Grmela, Roman; Skotakova, Alena; Rektor, Ivan (Acta neurologica Scandinavica, 2020)
OBJECTIVES: To evaluate effects of a six-month intensive dance-exercise intervention (DI) on cognition and brain structure in a mixed group of healthy seniors and people with mild cognitive impairment. METHODS: Subjects (aged ˃ 60 years with no dementia or depression) were randomly assigned to either a DI group or a life as usual (LAU) group. Detailed neuropsychological testing, measures of physical fitness and brain MRI encompassing T1 structural and diffusion tensor imaging (DTI) were performed at baseline and after 6 months. We assessed changes in cortical thickness and DTI parameters derived from tract-based spatial statistics. RESULTS: Altogether 62 individuals (n = 31 in the DI group) completed the protocol. The groups were matched for their demographic and clinical variables. After 6 months, we found significant cortical thickening in the right inferior temporal, fusiform and lateral occipital regions in the dancers compared to controls. Significant increases of radial and mean diffusivity were observed in various white matter tracts in the dancers; however, no differences were observed between the DI and LAU groups. The DI group as compared to the LAU group showed subtle improvements in executive functions. CONCLUSIONS: We observed DI-induced improvement in executive functions and increases of cortical thickness in the lateral occipitotemporal cortex which is engaged in action observation, visuomotor integration and action imitation, that is activities that are all important for motor learning and executing skilled movements.
Keywords: Aged; difuzní magnetická rezonance; DTI; lidé; lidé středního věku; tanec; senioři; ženské pohlaví; healthy seniors; dance-exercise intervention; MRI; Female; mužské pohlaví; terapie cvičením; cortical thickness; Middle Aged; Brain; mild cognitive impairment; cognitive; mozek; Neuropsychological Tests; kognice; Humans; neuropsychologické testy; Dancing; Cognition; Diffusion Magnetic Resonance Imaging; Exercise Therapy; Male; lateral temporo-occipital cortex